IDENTIFICATION OF BIOLOGICAL OXYGEN DEMAND (BOD) LEVELS AS AN INDICATOR OF WATER QUALITY IN THE UPSTREAM AND DOWNSTREAM OF THE BAGONG RIVER, BANYUWANGI: IDENTIFIKASI TINGKAT BIOLOGICAL OXYGEN DEMAND (BOD) SEBAGAI INDIKATOR KUALITAS AIR DI HULU DAN HILIR SUNGAI BAGONG, BANYUWANGI - Ardianingsih, Ardianingsih (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
This study aims to determine the levels of Biological Oxygen Demand (BOD) as an indicator of water quality in the upstream and downstream sections of the Bagong River, Banyuwangi, and to identify the factors influencing changes in BOD levels. Water samples were collected from two locations, namely Sungai Licin (upstream) and Sungai Bagong (downstream). BOD analysis was conducted at the Environmental Laboratory Unit of the Banyuwangi Environmental Agency using the Winkler titration method and five-day incubation. The results showed that the BOD level at the upstream location was 1.16 mg/L and at the downstream location was 0.92 mg/L, indicating relatively good water quality. Differences in BOD values between upstream and downstream are influenced by human activities, organic pollution, and environmental factors such as dissolved oxygen (DO) levels. This study emphasizes the importance of continuous water quality monitoring to protect the Bagong River ecosystem from further pollution.